Dinamika Kesejahteraan Psikologis Tahanan Pendamping Di Rumah Tahanan Kelas Iib Batusangkar - Mairoza, Vivi; Irman, Irman (Batanang : Jurnal Psikologi, 2022)
The purpose of this study was to determine the dynamics of the psychological well-being of accompanying prisoners in the Batusangkar Class IIB detention house. The method that the researcher uses is descriptive qualitative. The technique in collecting data that researchers used in this study was interviews. Based on the results of the study, it is known that the dynamics of psychological well-being of accompanying prisoners can be seen when they become escort prisoners, respondents can accept themselves well, establish close and warm relationships with other people, but there are also other respondents who have not been able to establish warm and intimate relationships with other people. , has independence in solving problems, is able to adapt to the current environment, has a purpose in life even though he is in punishment, and feels positive changes when he is a companion prisoner.┬áKeywords: psychological well-being, companion prisoner